Prospective cohort study of hospital inpatients with advanced cancer : cost analysis of a palliative care consultation team intervention - May, Peter (Trinity College (Dublin, Ireland). School of Medicine. Centre of Health Policy and Management, 2015)
The provision of care to people living and dying with serious chronic illness is a public health priority in most parts of the world. In a context of demographic change and shifting patterns of disease, the cost of care for this patient group is projected to grow substantially in the coming decades. Models of care that improve patient and family outcomes in a financially sustainable manner are urgently sought.
Keywords: Health Policy and Management, Ph.D.; Ph.D. Trinity College Dublin